Sistem Pengaturan Palang Pintu Kereta Api Terintegrasi Sensor Vibrasi, Proximity dan RTC Melalui Komunikasi Wireless - Abdullah; Ariski (MEANS (Media Informasi Analisa dan Sistem), 2022)
Research has been carried out on an integrated railroad crossing control system proximity sensor, vibration sensor and Real Time Clock (RTC) through wireless communication which can produce a monitoring and control system for railroad crossing gates automatically, knowing the effectiveness of NRF24l01 in providing data wirelessly to inputs that used (proximity sensors, vibration sensors, Real Time Clock), determine the effectiveness of the ATmega 328 microcontroller in processing all input and output data, and determine the work of automatic railroad crossing gates using three inputs (proximity sensors, vibration sensor, and RTC). The method applied in this research is the Research and Development or R&D method. The results of the tests that have been carried out prove that the system has been successfully integrated and effectively works according to the target, namely monitoring and controlling railroad crossing gates with a combination of vibration sensor, proximity sensors and Real Time Clock through wireless communication.